Systematic Literature Review: Penggunaan GeoGebra Terhadap Kemampuan Berpikir Kreatif Peserta Didik Dalam Pembelajaran Matematika - Sahira, Adinda; Nur, Iyan Rosita Dewi; Sari, Rika Mulyati Mustika (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
Learning mathematics today has many variations in learning, one of which is by using GeoGebra Software in learning mathematics. Mathematics in school learning requires the ability to reason, analyze calculations, and imagine in accordance with the ability to think creatively. The purpose of this research is to conduct a literature review related to Creative Thinking Ability in Junior High School Mathematics Learning. The method used in this research is SLR (Systematic Literature Review) on “Use of GeoGebra” and “Creative Thinking Ability” published in the last ten years from sinta and scopus indexed journals in Google Scholar. This study was guided by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) which resulted in 14 (fourteen) research articles to be systematically reviewed in 2014-2024 which were selected based on inclusion and exclusion criteria. The results showed that the use of GeoGebra on Creative Thinking Ability in Mathematics Learning was proven to significantly improve the ability of students with the application of learning models or not than conventional learning models.